Classifying cubic s-regular graphs of orders 22p and 22p² - Talebi, A.A.; Mehdipoor, N. (Algebra and Discrete Mathematics, 2013)
A graph is s-regular if its automorphism group acts regularly on the set of s-arcs. In this study, we classify the connected cubic s-regular graphs of orders 22p and 22p² for each s ≥ 1, and each prime p.